Impact and functionality of Oracle Islamic database system of Al-Arafah Islami Bank Limited - Naim, Fahim Ahmmed (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.